2019
DOI: 10.1021/acsami.9b07147
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Compliance Directs the Osteogenic Lineages of Stem Cells from the Human Apical Papilla via the Processes of Mechanosensing and Mechanotransduction

Abstract: It is well recognized that the interaction between stem cells and their physical microenvironment plays a fundamental role in controlling cell behaviors and directing lineage commitment, which eventually determines cell fate. Any change in the physical characteristics of the extracellular matrix in terms of topography, geometry, and stiffness has a strong effect on this interaction. Nevertheless, the precise biomechanism that regulates the responses of stem cells to the biophysical properties of substrates is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Dental papilla are present at the apex of immature teeth, thereby separated from dental pulp by an apical cell-rich zone. 28,29 Stem cells from apical papilla showed significantly high mineralization and proliferation. 30,31 Even in an immature tooth with pulp necrosis and AP, human apical papilla retained SCAP vitality.…”
Section: Discussionmentioning
confidence: 99%
“…Dental papilla are present at the apex of immature teeth, thereby separated from dental pulp by an apical cell-rich zone. 28,29 Stem cells from apical papilla showed significantly high mineralization and proliferation. 30,31 Even in an immature tooth with pulp necrosis and AP, human apical papilla retained SCAP vitality.…”
Section: Discussionmentioning
confidence: 99%
“…53 It has been demonstrated that the formation of FAs are related with the RhoA/ROCK signaling pathway influencing cell migration by affecting the cytoskeleton and cell contractility but it was also found that during osteogenic differentiation more FAs are beneficial for osteogenesis. 25,54,55 Previous study have reported that topographical dimension can provide significant stimulation to influence the formation of focal adhesion complexes. 24,56 The expression of FA in hBM-MSCs was assessed by immunofluorescence staining for vinculin and visualized by CLSM after 24 hours seeded onto the different substrates.…”
Section: Varied Mechanical Properties Mediated By Focal Adhesionsmentioning
confidence: 99%
“…As a member of the canonical Wnt pathway, overexpressing Wnt6 could enhance the osteogenic differentiation of human dental papilla cells (hDPCs) with up-regulated expression of mineralization-related genes such as alkaline phosphatase ( ALP ), Col1a1 , Ocn , Osteopontin , and Ibsp ( Wang et al, 2010 ). Wnt10a has been reported to regulate osteogenesis in mesenchymal stem cells, and T cell factor 1 ( Tcf-1 ), which is a nuclear transcription factor, potentially bound to the promoter region of Runx2 and determined the osteogenic lineage in stem cells from human apical papilla cells ( Zhou et al, 2019 ). Therefore, we detected expression of Wnt6 , Wnt10a , and Tcf-1 by in situ hybridization.…”
Section: Resultsmentioning
confidence: 99%